Pushing the boundaries of hemodialysis: innovations in membranes and sorbents - Olynka Vega-Vega; Claudio Ronco; Armando J. Martínez-Rueda (Permanyer, 2023)
Membranes and sorbents play a crucial role in extracorporeal blood purification therapies, which aim to remove harmful molecules and toxins from the blood. Over the years, advancements in hemodialysis (HD) membranes and sorbents have significantly enhanced their safety and effectiveness. This review article will summarize the latest breakthroughs in the development and clinical application of HD membranes and sorbents. We will commence with a concise examination of the mechanisms involved in solute transport across membranes and sorbents. Subsequently, we will explore the evolutionary path of HD membranes, from early cellophane membranes to high-flux membranes, including the development of high-cutoff membranes and the emergence of medium- cutoff membranes. We will discuss each type of HD membrane's advantages and limitations, highlighting the most promising advancements in novel biomaterials and biocompatibility, technologies, research in membrane performance, and their clinical applications. Furthermore, we will delve into the evolution and progress of sorbent technology, tracing its historical development, outlining its key characteristics, examining the mechanism involved in the adsorption process, and exploring its clinical application. This review aims to underscore the growth and future landscape of HD membranes and sorbents in extracorporeal blood purification techniques.